MODELLINIERTERGENERALISASIPADAVARIABELRESPONCACAH - , CHOLIFATUL HUSNA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
LinearModelhasbeenappliedduringthroughyearsinanalysingstatistics,especiallycontinuousdataanalysis.Thistechnicsbasedonassumptionatnormaldistributionintherandomcomponentandalsoexistenceoftherelationoflinearbetweenmeanwithsystemticcomponent(itsexplanatoryvariable).Thislinearmodelhereinafterexperiencesdevelopmentbygivingassumptionwhichmoreclearanceeitheratthedistributionoratrelationbetweenmanwiththesimetikcomponent.Distributiondatawillnolongerlimitedtonormaldistributionbutismemberfromdistributionofexponentialfamily.Thismodelnamed"GeneralizedLinierModels".ThismodelfirstlyisintroducedbyNelderandWedderburn(1972). Especiallyforthecountresponsevariable,generalizedlinearmodelswereusedPoissonregressionandNegativeBinomialregression.BothregressionwillbeappliedtothedatawiththecountresponsevariablewillbedonelaterwiththemodelselectioncriteriaAICtodeterminethebetGeneralizedLinearModel.